Contact zones photography, migration, and cultural encounters in the u.s. (LEUVEN UNIVERSITY PRESS, 2020)
Since the mid-nineteenth century photography has had a central place in cultural encounters within and between migrant communities. Migrant histories have been mediated through the photographic image, and the cultural practices of photography have themselves been transformed as migrant communities mobilise the photographic image to navigate experiences of cultural dislocation and the forging of new identities. Exploring photographic images and the cultural practices of photography as ?contact zones? through which cultural exchange and transformation takes place, this volume addresses the role of photography in migrant histories in the United States from the mid-nineteenth century to today. Taking as its focal point photography?s role in shaping migrant experiences of cultural transformation, and in turn how migrant experiences have re-configured culturally differentiated practices of photography, case studies on migration from Europe, Central America, and North America position photography as entwined with cultural histories of migration and cultural transformation in the United States.